Prática docente de uma professora de Educação Física: caminhos para a inclusão de alunos com Transtorno do Espectro Autista - Lima, Thiago Hallison Medeiros de (2017)
Autistic Spectrum Disorder (ASD) is defined as a condition related to qualitative difficulties in social interaction, language and repetitive and stereotyped movements. The enrollment of students with ASD in the regular school is relatively recent and awakens the educators in the challenges, at the same time that causes fear and doubts, since many teachers are accustomed to classes in traditional formats and not flexible. On the other hand, Physical School Education seems to be an adjunct to the process of including students with ASD, besides being a compulsory curricular component of Basic Education, it still promotes opportunities for the development of the subject as a whole, even in a context of differences. Our study object was centered on a biographical account of a Physical Education teacher and her experiences in basic education with children diagnosed with ASD. For, we were interested to know, as was the formation and the teaching practice of a Physical Education teacher regarding the inclusion of students with Autism Spectrum Disorder in their classes. Considering these aspects, our objective was to analyze the Physical Education teacher's practice to include the student with ASD from their reflections, as well as, in a specific way: analyze the teacher education of the Physical Education teacher for the inclusion of students with TEA; to describe conceptions of the Physical Education teacher regarding the inclusion of the student with ASD and also to analyze the expertise of the physical education teacher in the inclusion of students with ASD. This study is qualitative, of the descriptive exploratory type. The participant, and only informant of the research, was a Physical Education teacher, who worked in the regular school (public and private) and who had or already had students with ASD. For the data collection were used: observation; semi-structured interview and reflective sessions on the teacher's practice. In the analysis, the data were grouped into categories, namely: a) Special education in the initial and/or continued formation of the Physical Education teacher; b) The student with ASD: conceptions of a Physical Education teacher; and, c) Inclusive teaching practice: reports of the inclusion of students with ASD in Physical Education classes. With the analysis of the data, it was possible to verify that the teacher had little knowledge about the ASD and that she had participated in specific formative moments on the inclusion of the person with the disability, and no one with a focus on ASD. However, it was noticed that, although the teacher was looking for ways to keep informed, the use of scientific materials was restricted, this deepening was especially through informal conversations with other teachers, coordinators and parents of children with ASD. In his teaching practice we noticed relevance in the use and application of knowledge based on previous professional experience. Finally, even if the teacher did not have a broad scientific background on ASD, she always appeared to be open to the knowledge that was built within the school of action, together with the other teachers and all those who make up the school collective, especially with their students with ASD, as well as in meetings with parents of these students. Given this, we see the possibility of developing effective inclusive practices in favor of students with ASD. We also emphasize, and suggest that this study may be expanded, among other physical education teachers in the city of Maceió/AL, both public and private schools, so that we understand in depth how there has been training and teaching practice, especially recent graduates of the Physical Education course, who teach classes in class with students with ASD included, also suggesting formative actions that are based and adequate to the most urgent realities of these teachers and school community.